PKPU Moratorium as a Form of Proof of Default - Renda Aranggraeni; Dwi Wachidiyah Ningsih; Arkisman Arkisman; Moh Nasichin (Journal of Social Science, 2023)
The Bankruptcy and PKPU mechanism is the best debt moratorium at this moment because the creditor may estimate the debtor's ability to pay by looking at his good faith and the peace plan's debt moratorium. The surge in commercial court lawsuits and other economic repercussions led to the bankruptcy and PKPU moratorium, which is not the proper solution. If unsure, the moratorium can be reviewed. The moratorium on bankruptcy and PKPU cases is not an effective solution because bankruptcy institutions and PKPU were born from Law Number 37 of 2004, so the idea of a moratorium must go through a legislative process to be in sync with that law, which is difficult and takes a long time. Technically, this moratorium limits commercial courts' competence, requiring legislative and judicial responsibilities to be synchronized. Implementing it will generate several issues.